2021
DOI: 10.1088/1755-1315/662/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

The Service Quality of Kampoeng Kopi Banaran Agrotourism, Central Java Province, Indonesia

Abstract: Agro-tourism is a combination of tourism and farming activities that can be a solution to increase farmer income beyond production quantity’s value. Excellent service quality is the first step to agrotourism success. Therefore, this study analyses the Kampoeng Kopi Banaran agro-tourism’s service quality. The SERVQUAL, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI) methods are applied to estimate the service quality performance. Results suggest that Kampoeng Kopi Banaran agrotouris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Altamore et al (2018) stated that customer perception of a product shade and service has closely affected their emotion, whether positive or negative, and the intention of behaviour based on experience in a restaurant. Good and friendly quality service can make the customer satisfied (Mulyo et al, 2021). The high-quality service can make the user of the service feel satisfied (Mulyo et al, 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Altamore et al (2018) stated that customer perception of a product shade and service has closely affected their emotion, whether positive or negative, and the intention of behaviour based on experience in a restaurant. Good and friendly quality service can make the customer satisfied (Mulyo et al, 2021). The high-quality service can make the user of the service feel satisfied (Mulyo et al, 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Good and friendly quality service can make the customer satisfied (Mulyo et al, 2021). The high-quality service can make the user of the service feel satisfied (Mulyo et al, 2021). Expected quality by the customer is evaluated using an attribute in measuring food quality, service quality and physical environment quality (Zhang et al, 2019).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Furthermore, it is seen that scholars have limited focus on the exploration of agro-tourism customers' behaviors that can play a role in developing sustainable cities and communities. Previous literatures have mainly focused on agro-tourism satisfaction (Lachnidaki et al, 2021;Hussein and Rohman, 2021), agro-tourism service quality dimensions (Mulyo et al, 2021;Andayani et al, 2021) and agro-tourism development (Kubickova and Campbell, 2020;Rasulovich, 2021). However, several previous studies have examined the factors influencing behavioral intentions and actual behaviors toward agro-tourism, where Nakpathom and Pitchayadejanant (2017) have explored the determinants that affect visitor's intentions toward agro-tourism, Nguyen et al (2018) have identified that residents' attitudes have significant impact on their behaviors toward agro-tourism, Nishshanka et al (2019) have noted that tourists' attitude influences their willingness toward agro-tourism, Fern andez-Hern andez et al (2016) have mentioned that environmental concerns substantially influence visitors' behaviors toward agro-tourism, Zhao et al (2022) have stressed that attitudes and subjective norms have significant impacts on customers' intentions to participate in agrotourism, Zhong et al (2022) have measured that perceived value significantly influences farmer's green production and Suhud et al (2022) have examined the link between perceived value and behavioral intentions and found that perceived value has a significant effect on travel intentions in the coffee tourism perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is seen that scholars have limited focus on the exploration of agro-tourism customers’ behaviors that can play a role in developing sustainable cities and communities. Previous literatures have mainly focused on agro-tourism satisfaction (Lachnidaki et al , 2021; Hussein and Rohman, 2021), agro-tourism service quality dimensions (Mulyo et al , 2021; Andayani et al , 2021) and agro-tourism development (Kubickova and Campbell, 2020; Rasulovich, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The tourism industry is believed to be one of the mainstay sectors of the region to improve people's welfare (Irwan et al, 2021;Pitana and Gayatri, 2005). Concerning agriculture, there is a combined term between tourism and agriculture (Han et al, 2020), namely agrotourism, that introduces related agriculture in tourism packages (Lan and Hung, 2019;Maruti, 2009;Mulyo et al, 2021). Han et al, (2020) found that tourism and agriculture can help to sustain destinations by increasing tourist-stakeholder satisfaction.…”
Section: Introductionmentioning
confidence: 99%